Entry points for assessing ‘fair shares’ in national mitigation contributions - Setu Pelz; Gaurav Ganti; Shonali Pachauri; Joeri Rogelj; Keywan Riahi (Environmental Research Letters, 2025)
Fairness considerations have long been central to the international climate change mitigation discourse, generating numerous scientific and philosophical debates. Yet, there remains a pressing need for practical guidance on developing assertions of fairness in national mitigation contributions. The Paris Agreement mandates that subsequent nationally determined contributions (NDCs) submitted under Article 4 represent a progression compared to previous NDCs. Further decisions under the Paris Agreement mandate that NDCs include clear and transparent considerations of fairness, as recalled in the first Global Stocktake. We propose a practical approach to this, comprising a set of ‘entry points’ that represent key stages where decisions are taken in ‘fair share’ quantifications, from interpreting foundational principles to selecting indicators and presenting results. By bridging the gap between scholarly debates and practical application, this work supports the integration of clear and transparent fairness considerations into climate policy commitments. We demonstrate the use of our approach through a case study.